Producción Y Comercialización De Cacao En La Piladora San Miguel Del Recinto La Maravilla - Ordoñez Mayorga, Willian Jefferson (2017)
Our country is still recognized for its fine aroma cocoa since it has an excellent quality and production, being a very important item in the country's economy, ranking third of the state's main non-oil products. The present case study has as main scenario the San Miguel del Cantón Montalvo piling machine, La pilaadora was created with the objective of providing necessary services for the farmers of the sector and creating sources of work thus improving the quality of life of the community, the purpose of this work is to analyze the "Production and Marketing of Cocoa in the San Miguel piling of the La Maravilla", which will then give details in correlation to all the actions that are executed on the methods for the production of cacao, also the form in that the production is controlled, we will take into account the revenue generated by production during the months November, December and January corresponding to the years 2015 and 2016, I am aware of the shortcomings of the piling machine based on its accounting and production process , making comparisons of income and expenses for the periods 2015, 2016. Production and Marketing of Cocoa in the Piladora San Miguel del Recinto La Maravilla. The San Miguel piling machine is located in the Province of the Rivers, Canton Montalvo, La Maravilla Precinct, its creation is given with the objective of providing necessary services for the farmers of the sector and creating sources of work thus improving the quality of life of the community . Its legal framework, legal personality was registered in 1985, with Mr. MIGUEL ANGEL GAIBOR SECAIRA as its owner, starting its commercial activities as a rice miller. Its purpose is to serve the community of the sector and nearby areas of the same, the corresponding RUC is the natural person, ceased its activities in 2013 at the time of death Miguel Gaibor Secaira, they were restarted when the spouse of Don Miguel Gaibor took over the business activities.